2020
DOI: 10.1111/jonm.13192
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting work ability index among polish nurses working in hospitals – A prospective observational survey

Abstract: Aims To assess the ability to work of Polish nurses by age groups. Background The ability to work is widely discussed in the literature in the context of nurses' productivity; thus, it is necessary to identify the ability to work when facing an increasing demand for services. Methods The observational study involved 349 professionally active nurses aged 46.9 ± 9.7 years, with a length of service of 23.5 ± 9.6 years. The Work Ability Index (WAI) was used to assess the nurses' ability to work. Results The abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
4
11
0
3
Order By: Relevance
“…In our study, seniority was negatively associated with WA. This result is consistent with the findings of previous studies with Brazilian and Polish nurses (Fischer & Martinez, 2013 ; Rypicz et al., 2021 ). Since HCWs are exposed to high mental and physical demands, usually combined with adverse working conditions, the longer they remain active the higher is the risk of functional reduction and, consequently, of decreased WA (Fischer & Martinez, 2013 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, seniority was negatively associated with WA. This result is consistent with the findings of previous studies with Brazilian and Polish nurses (Fischer & Martinez, 2013 ; Rypicz et al., 2021 ). Since HCWs are exposed to high mental and physical demands, usually combined with adverse working conditions, the longer they remain active the higher is the risk of functional reduction and, consequently, of decreased WA (Fischer & Martinez, 2013 ).…”
Section: Discussionsupporting
confidence: 94%
“…The average WAI score found in this study (38.03) corresponded to the good WA level. Previous studies with Brazilian HCWs (Silva Junior et al., 2011 ; Vasconcelos et al., 2011 ) and in other developing countries such as Poland (Rypicz et al., 2021 ) have found similar scores, while studies conducted in developed countries, such as Israel and Italy, have demonstrated higher scores (Carel et al., 2013 ; Viola & Larese Filon, 2015 ). The combination of poorer working conditions, less favourable living and social conditions, quite present in developing countries, can aggravate health, well‐being and, consequently, WA (Eurofound & International Labour Organization, 2019 ; Fischer et al., 2002 ).…”
Section: Discussionmentioning
confidence: 89%
“…A total of 47 articles were excluded for the nominated reasons specified in Diagram 1: 44 from databases and 3 retrieved using alternative methods. Finally, 42 studies (Akodu & Ashalejo, 2019; Capelo et al, 2012; Carel et al, 2013; Das et al, 2019; Duran & Cocco, 2004; Ehegartner et al, 2020; Fischer & Martinez, 2013; Fonseca, 2012; Garosi et al, 2018; Golubic et al, 2009; Habibi et al, 2012; Hilleshein et al, 2011; Hoe et al, 2011; Izu et al, 2016; Knežević et al, 2010; Magnago et al, 2015; Maia et al, 2014; Fischer et al, 2006; Martinez et al, 2017; Martins, 2002; Melikidou & Sourtzi, 2014; Murassaki et al, 2013; Nery et al, 2013; Nowrouzi et al, 2015; Nunes et al, 2013; Oliveira, 2016; Pereira et al, 2021; Quispe Carbajal, 2021; Raffone & Hennington, 2005; Rodrigues et al, 2019; Rongen et al, 2014; Rostamabadi et al, 2017; Rotenberg et al, 2008, 2009; Rypicz et al, 2021; Silva et al, 2016, 2018, 2019; Sopajareeya, 2020; Sorić et al, 2013; Vasconcelos et al, 2011; Vilela et al, 2013) were included in the systematic review and 35 of them in the meta‐analyses performed.…”
Section: Resultsmentioning
confidence: 99%
“…The situation that the world and Poland faced because of the outbreak of the COVID-19 pandemic revealed many weaknesses and problems in the functioning of public systems, economic units, societies and institutions. We are now witnessing a joint international effort to contain and eradicate the virus, the emergence of which has paralyzed the economies of countries but above all exposed all the weaknesses https://doi.org/10.11118/978-80-7509-820-7-0255 256 of health systems (Campbell et al, 2013, Rypicz et al, 2020. Medical professionals play a special role during the fight against the pandemic.…”
Section: Introductionmentioning
confidence: 99%